STAGES OF DEVELOPMENT AND THE NEW IMAGE OF POLITICAL PARTIES IN UZBEKISTAN - Davron Mansurov; A. Safarov (Journals Park Publishing, 2023)
The article analyzes the development leaders of the political parties operating in the process of deepening democratic reforms and the formation of civil society in the Republic of Uzbekistan, and the ideologies they rely on.
Keywords: political party, ideology, civil society, democracy, political pluralism, electorate.